Comparing of organic nutrients digestibility in the feed rations containing lupin and peas in horses - Pavel Šajdler; Ladislav Zeman (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2005)
The aim of this study was to find out and compare organic nutrients digestibility in feed rations containing different forage legumes in balance trials on horses. The trials were always performed on a group of six sports horses (weight of 495 to 742 kg). Six feed rations were tested, which contained different proportion of certain forage legume in empirical feed mixtures. Three feed mixtures contained white lupine seeds (WLS) – Lu 0 (0.01% WLS), Lu 7 (7% WLS), Lu 14 (14% WLS) and surplus three feed mixtures contained field pea seeds (FPS) – Hr 0 (0.01% FPS), Hr 10 (10% FPS), Hr 20 (20% FPS). Amount of WLS in feed mixtures Lu 0 and Lu 7 was completed with starch to value 14% and amount of FPS in feed mixtures Hr 0 and Hr 10 was completed with starch to value 20%. Indicator method was used to predict dietary nutrients digestibility. Apparent digestibility values of all organic nutrients were higher at the feed rations with the content of FPS. Average values of apparent digestibility coefficient of those feed rations were: dry matter (77.79%; SD = 2.91), organic matter (78.43%; SD = 2.78), crude protein (79.89%; SD = 3.43), fat (66.57%; SD = 2.40), crude fiber (68.97%; SD = 3.21) and nitrogen-free extract (83.30%; SD = 2.71).